“Of mice and men”: values and liabilities of the athymic nude mouse model in anticancer drug development - Kelland, L.R. (European journal of cancer (1990), 2004)
Human tumour xenografts implanted subcutaneously (s.c.) into immunosuppressed mice have played a significant role in preclinical anticancer drug development for the past 25 years. Their use as a predictive indicator of probable clinical activity has been validated for cytotoxics. A retrospective analysis for 39 compounds where both extensive xenograft testing and Phase II clinical data were available, performed by the National Cancer Institute (NCI), has shown that 15/33 agents (45%) with activity in more than one-third of xenografts showed clinical activity ( P=0.04). However, with the exception of non-small cell lung cancer, activity within a particular histological type of the xenograft generally did not predict for clinical activity in the same tumour. Today, the question (largely unanswered) is how useful is the xenograft model (particularly the traditional s.c. model) in contemporary cancer drug discovery? There are many variables when conducting xenograft experiments which impact on outcome; viz, site of implantation, growth properties of the xenograft and size when treatment is initiated, agent formulation, scheduling, route of administration and dose and the selected endpoint for assessing activity. The xenograft model remains of value in current preclinical cancer drug development, especially when such studies give due consideration to the above variables and are based on sound mechanistic (e.g. status of the selected target in the chosen model) and pharmacological (e.g. use of formulated agent) principles. Dependent upon the drug target, a slowing of xenograft tumour growth (cytostatic effect) rather than tumour shrinkage might be the major observed effect. Human tumour xenografts are also particularly useful in determining pharmacodynamic markers of response for subsequent clinical application. Nevertheless, it needs to be kept in mind that the use of xenografts is relatively time-consuming and expensive, raises animal ethical issues and there are instances where the model is inappropriate as a likely predictor of clinical outcome (e.g. inhibitors of the metastatic process and anti-angiogenic strategies as the vasculature is of murine origin).